(untitled) (Agroindustria, Sociedad y Ambiente, 2021)
The study presented in the following scientific article was the implementation of interactive distance education as a modality in all institutions of the Educational Complex "Raul Quero Silva" through System Interactive Distance Learning (SAIA). The S.A.I.A establishes the educational and technical for the use of new electronic media in teaching principles – distance learning, as an alternative and complementary to classroom study, making programs Undergraduate, Postgraduate and Extension accessible. Reason requires the training of teachers and the implementation of S.A.I.A in all institutions of the said complex. This research is part of a quantitative model oriented field research descriptive. The validity of the same was done with a test trial of experts from the University Fermin Toro (UFT), to measure the reliability of the instrument method coefficient Cronbach’s alpha was applied, once the implementation of the instruments which were validated by two experts on the subject and a methodologist, information got up and proceeded to make their analysis by indicators, and then tabulate the results and graphically. As a result the implementation of SAIA was obtained in 99% of the institutions that make up the educational complex, the design of more than 60% of the virtual classrooms of the curriculum of studies and creation of a Virtual Research Center.